2022
DOI: 10.1128/spectrum.00957-22
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Surveillance of Carbapenem-Resistant Klebsiella pneumoniae from a Major Public Health Hospital in Singapore

Abstract: In this study, we characterized carbapenem-resistant Klebsiella pneumoniae clinical isolates collected over a 12-year period in the largest public acute-care hospital in Singapore using whole-genome sequencing. The results of this study demonstrate significant genomic diversity with the presence of well-known epidemic, multidrug-resistant clones amid a diverse pool of nonepidemic lineages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…The Infectious Diseases Society of America has issued a guidance on the treatment of CRE isolates, recommending BLBLIs as the preferred antibiotics for the treatment of most types of infections since carbapenemase-negative or KPC-producing pathogens prevailed in that region ( 15 ). Owing to the relatively high local MBL prevalence, these geographic-specific guidelines are not relevant in Singapore ( 16 , 17 ). However, our study found that ceftazidime-avibactam inhibited 80 to 90% of non-MBL-producing isolates.…”
Section: Discussionmentioning
confidence: 99%
“…The Infectious Diseases Society of America has issued a guidance on the treatment of CRE isolates, recommending BLBLIs as the preferred antibiotics for the treatment of most types of infections since carbapenemase-negative or KPC-producing pathogens prevailed in that region ( 15 ). Owing to the relatively high local MBL prevalence, these geographic-specific guidelines are not relevant in Singapore ( 16 , 17 ). However, our study found that ceftazidime-avibactam inhibited 80 to 90% of non-MBL-producing isolates.…”
Section: Discussionmentioning
confidence: 99%
“…One clade that carries ybt16 is limited to the north, whereas the clade with the ybt9 gene shows a nationwide distribution across six regions and twelve hospitals (Figure 7). The clade with the ybt16 gene also had GyrA-83Y and GyrA-87A mutations, while the clade with ybt9 had GyrA-83I mutations (Supplemental Table S1), showing the divergent evolutionary history of ciprofloxacin resistance in the two clades, driven by ciprofloxacin treatment [6]. The lineages in both clades carried virulence genes, i.e., the iuc locus and rmp on the Q97_2 plasmid, as well as multiple plasmid-borne carbapenemase genes, bla OXA-48 , bla OXA-181 , bla NDM-1 , bla NDM-5 and bla KPC-2, independently (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…The evolution of multidrug-resistant K. pneumoniae is characterized by the expansion of clones at the hospital level driven by nosocomial transmission routes, followed by regional and global expansion due to strong selective pressure from antimicrobial agents. The local epidemiological and clinical characteristics of K. pneumoniae have been reported in multicentre studies in different countries [6, 33, 4042], revealing expansions of both endemic clones and imported clones, with clonal expansion mostly caused by the globally known ST258 lineage. Our results concur with the findings of these studies, showing similar clonal expansion of globally and regionally circulating clones in the KSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome data found that both the K. pneumoniae isolates have different STs and showed no clonal relationship with the global tet(X4)-positive K. pneumoniae strains in the NCBI database indicative of genetic diversity. Additionally, single tet(X4)-positive E. coli isolate belonged to ST746 which have been previously associated with carbapenem resistance in Korea 32 and China 33 . It has been suggested that mobile genetic element not the clones play an important role in tet(X4) transmission 27 .…”
Section: Discussionmentioning
confidence: 96%